Growth Promoting Effects of Endophytic Bacteria from Vanda sp. on Tissue-Cultured Seedlings - Ani Yuyun Sari (Jurnal Agroteknologi dan Inovasi Pertanian, 2025)
Endophytic bacteria live and associate with plant tissues during their life in nature without causing disease and have the potential as plant growth promoters (PGPR). However, in tissue culture techniques, the sterilization process is known to kill a number of endophytic bacteria in plants resulting from tissue culture. This study aims to explore the potential of endophytic bacteria from the epiphytic orchid Vanda sp. as a growth-stimulating agent in tissue-cultured orchid seedlings. The method used in this study is through a series of experiments including the process of isolation, characterization, and testing the potential of endophytic bacteria as Plant Growth Promoting (PGP) on the growth of roots and new leaves and amylum content in the root tissue of plants resulting from tissue culture. A total of 29 isolates of endophytic bacteria were successfully isolated. All isolates showed potential as PGPR through IAA production tests, dissolution of phosphate, and nitrogen fixation. Isolate EA4(5) was selected as a superior isolate with the highest IAA production (15.16 µg/mL), high phosphate solubilization index (1.143 cm) and able to grow on nitrogen-free media. Inoculation of selected isolates on orchid Dendrobium sylvanum seedlings from tissue culture showed that soaking the roots for 2 hours was able to give the best results with a growth percentage of new roots by 70% and new leaves by 10%. Amylum content in the root tissue also increased in plants that had been inoculated with endophytic bacteria.